Mejorando la mentoría en la educación universitaria y explorando las implicaciones para el aprendizaje en línea - Andersen, Camey L.; West, Richard E. (Revista de Educación a Distancia (RED), 2020)
This article is a literature review of mentoring and higher education academic literature from 2008-2018. The review analyzed what makes an effective mentor and what are the implications of practice for those strategies. This article is for higher education leaders, mentoring programs, and mentors who want to improve their traditional and online mentoring programs and mentoring practices. After narrowing the search terms, the researcher searched EBSCO and ERIC databases and this search produced a combined total of 256 results. These articles were further narrowed to 34 articles that met the keyword search and exclusion criteria. The remaining articles are the focus of the literature review analysis for mentoring and higher education literature. The review produced three major themes of impact of mentoring, role of mentor, and mentoring programs, as well as implications for practice for each theme. The researcher further examined the themes in detail and provided information about retention, persistence, long-term benefits of mentoring, student interaction, student support, role models, types of mentoring programs, platforms for mentoring, and mentor training. The review concludes with suggestions for further research, including recommendations for mentor training and online mentoring.